Why Is Parental Resilience Necessary? Phenomenological Study of The Level of Parental Resilience In Assisting Children To Learn From Home/ Mengapa Ketahanan Orangtua Diperlukan? Studi Fenomenologi Tingkat Resiliensi Orangtua Dalam Mendampingi Anak Belajar Dari Rumah - Solichah, Novia; Shofiah, Nurul (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Abstract: Covid-19 Pandemic outbreak has become a global disease that has spread to every country in the world. Society is faced by a significant change in the order of social life. All activities are taught using daring methods. These things are the cause of many people experiencing problems such as increased anxiety and stress. It also affects parents who are forced to adapt to new realities and tend to feel stressed in accompanying children to learn daring. These things are the cause of many people experiencing problems such as increased anxiety and stress. It also affects parents who are forced to adapt to new realities and tend to feel stressed in accompanying children to learn daring. With this condition, it is important for parents to have resilience in the face of stress called resilience. The purpose of this study is to explain the importance of the role of parental resilience during the mentoring of home learning programs through the level of resilience and patterns of parental resilience during the mentoring of learning activities. The method used in this study is qualitative method with phenomenological approach. The analysis unit of this study is parents who accompany children to learn daring during the pandemic for approximately 1 year at least, from the level of grade 1-3 elementary school numbering 25 parents. The results showed that parental resilience is indispensable to motivate the child's learning, provide a sense of comfort and safety to the child, make the child happy during learning. This is shown through the results of quantitative surveys of parental resilience levels in the high category. Second, parental resilience patterns are shown by aspects of emotional regulation, impulse control, optimistic attitudes, empathy, problem analysis skills, and improved positive aspects.Keywords: Resilience; Parental Assistance; Studi from HomeAbstrak: Wabah Pandemi Covid-19 menjadi penyakit global yang telah menyebar ke setiap negara dunia. Masyarakat dihadapkan oleh perubahan tatanan kehidupan sosial yang signifikan.Â Seluruh kegiatan salah satunya belajar mengajar menggunakan metode daring. Berbagai hal ini menjadi penyebab banyak orang mengalami permasalahan seperti peningkatan kecemasan dan stress. Hal ini juga berdampak pada orangtua yang terpaksa beradaptasi dengan realitas baru dan cenderung merasa stress dalam mendampingi anak belajar daring. Dengan kondisi demikian, maka para orangtua penting untuk memiliki ketahanan diri dalam menghadapi stress yang disebut resiliensi. Tujuan dari penelitian ini yakni untuk memaparkan pentingnya peran ketahanan orangtua selama pendampingan program belajar dari rumah melalui tingkat resiliensi dan pola resiliensi orangtua selama pendampingan kegiatan belajar. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan fenomenologi. Unit analisis dari penelitian ini yakni orangtua yang mendampingi anak belajar daring di masa pandemi kurang lebih selama 1 tahun minimal, dari jenjang kelas 1-3 SD berjumlah 25 orangtua. Hasil penelitian menunjukkan bahwa resiliensi orangtua sangat diperlukan untuk memotivasi belajar anak, memberikan rasa nyaman dan aman pada anak, membuat anak senang selama belajar. Hal tersebut ditunjukkan melalui hasil survei kuantitatif tingkat resiliensi orangtua dalam kategori tinggi. Kedua, pola resiliensi orangtua ditunjukkan dengan aspek regulasi emosi, pengendalian impuls, sikap optimis, empati, kemampuan analisis masalah, dan peningkatan aspek positif.Kata Kunci: Ketahanan; Resiliensi; Pendampingan Orangtua; Belajar Dari Rumah